2016
DOI: 10.3389/fnins.2015.00500
|View full text |Cite
|
Sign up to set email alerts
|

Turning On Lights to Stop Neurodegeneration: The Potential of Near Infrared Light Therapy in Alzheimer's and Parkinson's Disease

Abstract: Alzheimer's and Parkinson's disease are the two most common neurodegenerative disorders. They develop after a progressive death of many neurons in the brain. Although therapies are available to treat the signs and symptoms of both diseases, the progression of neuronal death remains relentless, and it has proved difficult to slow or stop. Hence, there is a need to develop neuroprotective or disease-modifying treatments that stabilize this degeneration. Red to infrared light therapy (λ = 600–1070 nm), and in par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
93
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(98 citation statements)
references
References 122 publications
2
93
0
3
Order By: Relevance
“…In this review, we have summarized the up-to-date literature reports about medical uses of IR radiation, including neural stimulation (direct activation of neural tissue by IR radiation), photoaging (emerging evidence that IR can have biphasic effects on the skin), antitumor action (IR can inhibit cancer cell proliferation and potentiate the therapeutic effectiveness of chemotherapy), and brain neuroprotection (novel neuroprotective treatments for stroke, TBI and neurodegenerative disorders (IR radiation therapy for Alzheimer's and Parkinson's diseases [134]). Clinical evidence has demonstrated that IR can selectively induce cell death by apoptosis, necrosis and anoikis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review, we have summarized the up-to-date literature reports about medical uses of IR radiation, including neural stimulation (direct activation of neural tissue by IR radiation), photoaging (emerging evidence that IR can have biphasic effects on the skin), antitumor action (IR can inhibit cancer cell proliferation and potentiate the therapeutic effectiveness of chemotherapy), and brain neuroprotection (novel neuroprotective treatments for stroke, TBI and neurodegenerative disorders (IR radiation therapy for Alzheimer's and Parkinson's diseases [134]). Clinical evidence has demonstrated that IR can selectively induce cell death by apoptosis, necrosis and anoikis.…”
Section: Discussionmentioning
confidence: 99%
“…IR is divided into different bands: Near-Infrared (NIR, 0.78~3.0 μm), Mid-Infrared (MIR, 3.0~50.0 μm) and Far-Infrared (FIR, 50.0~1000.0 μm) as defined in standard ISO 20473:2007 Optics and photonics -- Spectral bands [1]. Several studies have reported that IR can improve the healing of skin wounds, photoprevention, relieve pain, stiffness, fatigue of rheumatoid arthritis, ankylosing spondylitis, potentiate photodynamic therapy, treat ophthalmic, neurological, and psychiatric disorders, and stimulate the proliferation of mesenchymal and cardiac stem cells [19]. …”
Section: Introductionmentioning
confidence: 99%
“…Likewise, our recent study also demonstrated the remarkable action of LLI to attenuate depression-like behaviors and related ATP biosynthesis decline by facilitating mitochondrial CCO activity in the prefrontal cortex (Xu et al, 2016). Intriguingly, recent studies of Aβ-induced cell injury have suggested a potential role for LLI in the treatment of neurodegenerative disease (Farfara et al, 2015; Johnstone et al, 2015; Meng et al, 2013; Song et al, 2012). Particularly, a previous in vitro study involving LLI on Aβ-treated mouse hippocampal neurons displayed a robust increase in brain-derived neurotrophic factor expression and strong amelioration in dendritic atrophy (Meng et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This approach consists in illuminating large volume of tissues with red or near infrared light to stimulate non-specifically the cells via mechanisms that are thought to involve absorption by cytochrome-oxydase and further activation of the mitochondria metabolism. The technique is under active review for use in a vast range of brain diseases including stroke, traumatic brain injury, neurodegenerative diseases, where the non-specific optical stimulation of the cortical tissue was shown in mice models to lead to transient increase of ATP, decrease of inflammatory markers and -in some studies-cognitive improvement (reviews in [17,18] and first studies in humans of the use of PBM to alleviate Alzheimer's disease symptoms in [19]). …”
Section: Introductionmentioning
confidence: 99%